Quality of Work Life and Job Satisfaction among Journalists of Television Newsrooms in Kathmandu (People's Journal of Management, 2023)
This descriptive research study is conducted among journalists in television newsrooms in Kathmandu identifies that safe working conditions, adequate health benefits, and equitable compensation are critical factors in enhancing job satisfaction among journalists. Job autonomy, opportunities for professional development, social responsibility, and positive image are also significant in fostering employee satisfaction which is in line with past literature on workplace safety, employee satisfaction, and perception of work environment among journalists. The study's results suggest that companies should create a positive work atmosphere by compensating employees fairly, providing opportunities for professional growth, and fostering a culture of social responsibility and positive image.